Adjusting the Warm-Glow Thermostat: How Incentivizing Participation in Voluntary Green Programs Moderates Their Impact on Service Satisfaction - Giebelhausen, Michael; Chun, HaeEun Helen; Cronin, J. Joseph; Hult, G. Tomas M. (Journal of Marketing, 2016)
In Study 1, the authors find that people are more satisfied with a service experience when they choose to participate in the provider's voluntary green program (e.g., recycling)—an effect mediated by the “warm glow” of participation. The downside, however, is that this same mechanism decreases satisfaction among people who choose not to participate. In Study 2, analysis of data from the J.D. Power Guest Satisfaction Index suggests that incentivizing the program (i.e., compensating the program participants) paradoxically increases satisfaction for those who do not participate but decreases satisfaction among those who do. Studies 3 and 4 explore how manipulating incentive characteristics might enable managers to maximize satisfaction for both groups. Study 3 indicates that, compared with no incentive, an “other-benefiting” incentive increases warm glow and satisfaction for green program participants but decreases them among nonparticipants. Study 4, however, suggests that mixed incentive bundles (i.e., providing both self-benefiting and other-benefiting options) maximize warm glow and satisfaction for both groups—the ideal outcome for managers.